Review of fig wasps (Hymenoptera: Chalcidoidea: Agaonidae & Pteromalidae) associated with Ficus (Moraceae) in South Korea, with descriptions of two new species - Kim, Moo-Sung; Park, Duk-Young; Choi, Subin; Lee, Seunghwan; Kim, Il-Kwon (Zootaxa, 2026)
This study presents the first comprehensive review of South Korean fig wasps (Hymenoptera: Chalcidoidea: Agaonidae, Pteromalidae) associated with Ficus. Two new species, Wiebesia confusa Park & Kim, sp. nov. (Agaonidae) and Philotrypesis bicolor Park & Kim, sp. nov. (Pteromalidae), were reared from the figs of Ficus oxyphylla (=F. sarmentosa var. nipponica, Moraceae). Furthermore, two additional agaonid species, Blastophaga nipponica Grandi, 1922 and Wiebesia pumilae (Hill, 1967), and a pteromalid species, Sycoscapter inubiae (Ishii, 1934), are formally recorded from South Korea for the first time. The mitochondrial cytochrome c oxidase subunit I and cytochrome b genes were used to corroborate the morphological identification of the wasps. A key to Korean species, descriptions, diagnoses and host plant records are provided, along with detailed images of morphological characters for each species.